2014
DOI: 10.1007/s13594-014-0183-4
|View full text |Cite
|
Sign up to set email alerts
|

Cow’s milk as a dietary source of equol and phenolic antioxidants: differential distribution in the milk aqueous and lipid fractions

Abstract: International audienceCow’s milk contains bioactive secondary phenolic compounds that are formed by bovine’s gut bacterial flora from plant phenolic compounds. Equol, a metabolite of daidzein, is one such secondary compounds of biological interest. The potential of phenolic compounds in milk as dietary antioxidants and their distribution within the milk matrix were examined. The equol concentrations, total phenolic contents, and antioxidant activity (Trolox equivalent antioxidant capacity and inhibition of F2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 18 publications
0
21
1
2
Order By: Relevance
“…This means that equol is not a particularly lipophilic compound and therefore has little affinity with the lipid milk fraction. This interpretation goes against a recent study, however, where the authors reported that equol is distributed to a larger extent in the lipid fraction than in the aqueous fraction and therefore that the skimming process reduces the amount of equol in cow's milk (Tsen et al 2014). More research is needed to clarify this situation, but this initial screening indicated that equol did not seem to be affected by the lipid fraction in milk.…”
Section: Equol Content Of Commercial Milk In Belgiumcontrasting
confidence: 64%
See 1 more Smart Citation
“…This means that equol is not a particularly lipophilic compound and therefore has little affinity with the lipid milk fraction. This interpretation goes against a recent study, however, where the authors reported that equol is distributed to a larger extent in the lipid fraction than in the aqueous fraction and therefore that the skimming process reduces the amount of equol in cow's milk (Tsen et al 2014). More research is needed to clarify this situation, but this initial screening indicated that equol did not seem to be affected by the lipid fraction in milk.…”
Section: Equol Content Of Commercial Milk In Belgiumcontrasting
confidence: 64%
“…An alternative strategy for making equol's health benefits available to everyone would be the supply of this molecule in the human diet via food of animal origin. From the range of foods commonly consumed by humans, milk from dairy cows is an interesting potential source of equol (Tsen et al 2014;Křižová et al 2011). In recent years, many studies have been conducted on how to assess equol in milk and on feeding strategies for increasing the content of this molecule in milk (Adler et al 2014;Kalač 2013;Höjer et al 2012;Andersen et al 2009;Mustonen et al 2009;Steinshamn et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these may also be formed from amino acids. Dairy milk is thus a good source of several PCs including equol and phenolic antioxidants (Tsen et al, 2014). These shown to improve milk quality when supplemented to the diet of dairy cows (Aguiar et al, 2014).…”
Section: Applications In Dairy Productsmentioning
confidence: 99%
“…In addition to a protein fraction, antioxidant peptides, uric acid, CLA and lipophilic vitamins, milk also contains bioactive secondary phenolic compoundssuch as equol, a metabolite of daidzeinwhich are formed from plant phenolics by the bacterial flora of the cow intestine (54) . Tsen et al (55) analysed five commercial whole milk, four commercial semi-skimmed milk and three commercial skimmed milk samples purchased from local supermarkets in Singapore and found that the antioxidant capacity and the ability to inhibit the formation of F 2 -isoprostanes increased with the concentrations of phenolic compounds and equol. However, differences in the antioxidant potential were not as marked as the differences in the equol concentration, indicating that other compounds contributed to the antioxidant potential.…”
Section: Nutrition Research Reviewsmentioning
confidence: 99%